2001
DOI: 10.1007/s004250000420
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic characterization of the recombinant Arabidopsis thaliana nitrilase subfamily encoded by the NIT 2/ NIT 1/ NIT 3-gene cluster

Abstract: Three of the nitrilase isoenzymes of Arabidopsis thaliana (L.) Heynh. are located on chromosome III in tandem and these genes (NIT2/NIT1/NIT3 in the 5'-->3' direction) encode highly similar polypeptides. Copy DNAs encompassing the entire coding sequences for all three nitrilases were expressed in Escherichia coli as fusion proteins containing a C-terminal hexahistidine extension. All three nitrilases were obtained as enzymatically active proteins, and their characteristics were determined, including a detailed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
168
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(182 citation statements)
references
References 32 publications
9
168
0
1
Order By: Relevance
“…This observation was independently verified for NIT1 in a recent study appearing in print during the preparation of this manuscript (Osswald et al 2002). IAM went undetected by the GC-MS technique used in our previous work which included methylation of samples and focussed on acidic metabolites (Vorwerk et al 2001).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…This observation was independently verified for NIT1 in a recent study appearing in print during the preparation of this manuscript (Osswald et al 2002). IAM went undetected by the GC-MS technique used in our previous work which included methylation of samples and focussed on acidic metabolites (Vorwerk et al 2001).…”
Section: Discussionsupporting
confidence: 56%
“…In a preliminary earlier report, it was stated that all four A. thaliana nitrilases would convert IAN to IAA with a side-product of IAM noted on thin-layer (Bartel and Fink 1994). However, this reaction product was neither identified unambiguously in that study ñor has it been confirmed in later studies that NIT4 uses IAN as a substrate (Vorwerk et al 2001). Thus, a re-examination was carried out using recombinant NIT1, NIT2 and NIT3 in highly purified form.…”
Section: Purification Of Iam and Analysis By Gas Chromatography-tandementioning
confidence: 88%
See 3 more Smart Citations